GROUND DEFORMATION MONITORING BY CONVERGENCE MEASUREMENT AND DAMAGED AREA MAPPING IN DEEP ORE ZONE (DOZ) MINE AT PT. FREEPORT INDONESIA - Andre Sebastiano Ginting; Hadnaltias Alpeki (PERHAPI, 2018)
Deep Ore Zone (DOZ) Mine is an underground mine with block caving method within The East Erstberg Skarn System (EESS) deposit. Safe ground condition is the most important thing on production stage related to safety of employees and property in underground. Rockfall is one of fatal risks for employees who work in underground. It happens when ground deformation getting worse. The deformation monitoring is a needed to observe the behavior of rock mass, early detection of hazards, and evaluate current ground support system. The damaged ground in DOZ Mine on production stage is mainly caused by stress around the pillar. It has related to the lifetime of DOZ Mine approximate 3 years left. No mucking activity causes rock wegdes above the pillar and total load for pillars strength. There is maximum stress and strain rock of pillar which it will be broken ground when the stress and strain pass through the maximum value. The type categories of damaged are slight damage, moderate damage, heavy damaged, and squeeze or collapse ground. Those damaged type have to be recorded on a damaged area map for a comparison with other monitoring data. Convergence measurement is one of methods to monitor ribs ground displacement. Strain in rock masses represents its change in length from its orginal length. Convergence measurement is one of methods to monitor ground displacement, especially the strain between two ribs on a panel. The station installed on each ribs of drawpoint of active panel and fix facilities area. The significant value of displacement by convergence measurement is more than cummulative 75 mm. Based on those informations, the ground support dan panel rehabilitation can be consider needed or not. The area with significant value and oberserved damaged ground will be proposed a rehabilitation for safety work area. For example, we found increasing trend displacement followedby moderate damaged observed. The significant displacement found at Panel 04around Drawpoint 18W to 19W. We proposed a rehabilitation for this area after aweek from the day of significant displacement measurement. Rehabilitation hasproposed when the increasing trend was higher to prevent ground become broken or unsafe condition.